Analisis Pemahaman Konsep Pembagian Dalam Pembelajaran Matematika Siswa Kelas II SDN 20 Tanjung Keramat - Megawati; Waridah; Linda Dwi Saputri (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2026)
Abstract: This study aims to determine the understanding and difficulties of second-grade students at SD Negeri 20 Tanjung Keramat in comprehending the concept of division in mathematics learning. The research employed a qualitative approach with a descriptive method. The subjects of the study consisted of teachers and students, while the research object focused on students’ conceptual understanding of division. Data were collected through interviews and tests using question sheets and interview guides. The results revealed that students’ understanding of the concept of division was still low. In the multiple-choice test, 86.66% of students were categorized as “poor,” while in the essay test, 66.66% also demonstrated low understanding. Students were unable to identify the meaning of division as a process of grouping or repeated subtraction and faced difficulties in relating word problems to division operations. The main contributing factors included errors in selecting arithmetic operations, weak concrete and symbolic representations, poor understanding of the division symbol “:”, and limited comprehension of problem statements. Keywords: Conceptual Understanding, Division, Learning Difficulties, and Elementary Mathematics. Abstrak: Penelitian ini bertujuan untuk mengetahui pemahaman dan kesulitan siswa kelas II SD Negeri 20 Tanjung Keramat dalam memahami konsep pembagian pada pembelajaran matematika. Penelitian menggunakan pendekatan kualitatif dengan jenis deskriptif. Subjek penelitian terdiri atas guru dan siswa, sedangkan objek penelitian difokuskan pada pemahaman konsep pembagian. Data dikumpulkan melalui wawancara dan tes menggunakan lembar soal serta panduan wawancara. Hasil penelitian menunjukkan bahwa pemahaman siswa terhadap konsep pembagian masih rendah. Pada tes pilihan ganda, 86,66% siswa berada pada kategori “kurang”, sedangkan pada tes esai, 66,66% juga menunjukkan pemahaman rendah. Siswa belum mampu mengidentifikasi makna pembagian sebagai proses pengelompokan atau pengurangan berulang dan kesulitan mengaitkan soal cerita dengan operasi pembagian. Faktor penyebab utama meliputi kesalahan memilih operasi hitung, lemahnya representasi konkret dan simbolis, kurangnya pemahaman simbol “:”, serta keterbatasan dalam memahami kalimat soal. Kata Kunci: Pemahaman Konsep, Pembagian, Kesulitan Belajar, dan Matematika Sekolah Dasar.